The Language Attitudes of the Member of Aristocracy of Mambalan Village towards High Sasak Language - Zainudin Abdussamad; Sutarman Sutarman; Abdul Muhid; Diah Supatmiwati; Wiya Suktiningsih; Wahyu Kamil Syarifaturrhaman; Dedi Aprianto (LPPM Universitas Bumigora Mataram, 2023)
Noblemen, generally, appreciate their own language as social status in a community. However, Noblemen in Mambalan village have different attitude toward their language. This research aims at finding out the attitude of noblemen in Mambalan village towards their own language. It implements qualitative methods to explain the results of the research. Data are collected via questionnaire which are given to the selected informants; they are about 50 informants with age range between 21-50. The questionnaire is divided into two parts; the first questionnaire aims at confirming their social status and the second questionnaire relates to the language they use in daily communication. The results show that the noblemen of Mambalan village have negative attitudes toward the high Sasak language. This negative attitude induces a gradual decrease in the existing values which eventually influence the pride of the member of the aristocracy of Mambalan village to use high Sasak language. A predominant example of this decreasing value is apparent in their preference for utilization of Bahasa Indonesia and low Sasak language rather than the use of high Sasak language. They regard Bahasa Indonesia and low Sasak language to be more prestigious than high Sasak language and consider it as the appropriate tool of communication in their daily interaction and social communication.